SARS-CoV-2 Infection in One Cat and Three Dogs Living in COVID-19-Positive Households in Madrid, Spain - Miró, Guadalupe; Regidor-Cerrillo, Javier; Checa, Rocio; Diezma-Díaz, Carlos; Montoya, Ana; García-Cantalejo, Jesús; Botías, Pedro; Arroyo, Javier; Ortega-Mora, Luis-Miguel (Frontiers in Veterinary Science, 2021)
In this study, we describe SARS-CoV-2 infection dynamics in one cat and three dogs from households with confirmed human cases of COVID-19 living in the Madrid Community (Spain) at the time of expansion (December 2020 through June 2021) of the alpha variant (lineage B.1.1.7). A thorough physical exam and nasopharyngeal, oropharyngeal, and rectal swabs were collected for real-time reverse-transcription PCR (RT-qPCR) SARS-CoV-2 testing on day 0 and in successive samplings on days 7, 14, 21 and 47 during monitoring. Blood was also drawn to determine complete blood counts, biochemical profiles, and serology of the IgG response against SARS-CoV-2. On day 0, the cat case 1 presented with dyspnoea and fever associated with a mild bronchoalveolar pattern. The dog cases 2, 3 and 4 were healthy, but case 2 presented with coughing, dyspnoea and weakness, and case 4 exhibited coughing and bilateral nasal discharge three and six days before the clinical exam. Case 3 (from the same household as case 2) remained asymptomatic. SARS-CoV-2 detection by RT-qPCR showed that the cat case 1 and the dog case 2 exhibited the lowest cycle threshold (Ct) (Ct < 30) when they presented clinical signs. Viral detection failed in successive samplings. Serological analyses revealed a positive IgG response in cat case 1 and dog cases 3 and 4 shortly after or simultaneously to virus shedding. Dog case 2 was seronegative, but seroconverted 21 days after SARS-CoV-2 detection. SARS-CoV-2 genome sequencing was attempted, and genomes were classified as belonging to the B.1.1.7 lineage.